IS PROJECT BASED LEARNING THE WAY TO GO? - Patnaikuni, Indubhushan; Myadaraboina, Himabindu (Proceedings of International Structural Engineering and Construction, 2016)
Many educational institutions have moved or are moving to project-based learning (PBL) in Engineering. Project-based learning and problem-based learning have both advantages and also disadvantages. They are suitable for certain courses and may not be that helpful for certain other courses. In case of courses which require mathematical and analytical skills PBL does not seem to be very useful. As a matter of fact, many students do not seem to learn the basics/fundamentals if PBL method is used. Courses like statics, Mechanics, and structural analysis are the type of courses which can produce graduates without a proper fundamental understanding of the subject matter if PBL is used for the entire course.